Group standardization of Chinese experts specification of operating techniques for facial embedded thread lift - Shi, Bing (Frontiers in Surgery, 2026)
BackgroundDespite the global popularity of minimally invasive thread lifts, the absence of standardized protocols has led to significant variations in outcomes. This study establishes China's first expert consensus (T/CAPA 009-2023) on facial thread lift techniques, addressing critical gaps in operator training, material selection, and anatomical precision.MethodsA multidisciplinary panel analyzed 2,143 PPDO thread procedures (2018–2022) across 35 institutions. The consensus framework integrates: 1) Graded facility/operator requirements (Grade III device management), 2) Anatomical stratification (SMAS, fat layers, ligament anchoring), and 3) Region-specific protocols (upper/mid/lower face, neck) with 14 illustrated surgical designs.ConclusionMulticenter data and anatomical studies demonstrate that this consensus framework improves thread lift safety and efficacy, though further RCTs are warranted to confirm long-term outcomes The hierarchical protocol serves as a global benchmark for aesthetic training programs, particularly in Asian facial anatomy.